2014
DOI: 10.1016/j.scitotenv.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the abundance and community structure of soil ammonia oxidizers in a wet sclerophyll forest under long-term prescribed burning

Abstract: • We examined how fires affected the abundances and communities of soil AOB and AOA.• A long-term repeated forest fire experiment was investigated.• Fires increased the abundance of bacterium amoA genes, but not archaeal amoA genes.• Fire also modified the composition of AOA and AOB communities.• AOB genotype was affected by soil pH and DOC, while AOA by nitrate-N and DOC. a b s t r a c t a r t i c l e i n f o Fire shapes global biome distribution and promotes the terrestrial biogeochemical cycles. Ammonia-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 47 publications
(48 reference statements)
2
7
1
Order By: Relevance
“…The Shannon index in acidic soils was lower than that in neutral soils, and the impacts of pH, SOC, and TN on the AOB community composition had been observed in this study, indicating that pH, SOC, and TN are important factors affecting AOB in paddy soils in Southern China. The consistent results were also observed in rice paddy soils (Long et al 2014;Zhang et al 2012) and sediments (Mosier and Francis 2008). Clusters 1, 2, 8a, and 8b containing major AOB sequences in acidic soils and cluster 4 affiliating within the genus of Nitrosospira were correlated with PNA, indicating that clusters 1, 2, 8a, and 8b might contribute more to nitrification ability in acidic soils.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The Shannon index in acidic soils was lower than that in neutral soils, and the impacts of pH, SOC, and TN on the AOB community composition had been observed in this study, indicating that pH, SOC, and TN are important factors affecting AOB in paddy soils in Southern China. The consistent results were also observed in rice paddy soils (Long et al 2014;Zhang et al 2012) and sediments (Mosier and Francis 2008). Clusters 1, 2, 8a, and 8b containing major AOB sequences in acidic soils and cluster 4 affiliating within the genus of Nitrosospira were correlated with PNA, indicating that clusters 1, 2, 8a, and 8b might contribute more to nitrification ability in acidic soils.…”
Section: Discussionsupporting
confidence: 81%
“…Among these factors, increasing lines of evidence has suggested that soil pH plays the most dominant role in controlling the abundance and distribution of AOA and shaping the distinct ecological niches of AOA and AOB. Diverse researches have elaborated the microbial community composition and abundance of AOA and their bacterial counterparts AOB in various ecosystems (Chen et al 2008(Chen et al , 2010(Chen et al , 2011He et al 2007;Yao et al 2011;Li et al 2011;Pester et al 2012;Shen et al 2012;Hu et al 2013Hu et al ,2014Long et al 2014;Wang et al 2015;Jiang et al 2015). However, most of these investigations focused on a locational samples or a limited number of soil samples.…”
Section: Introductionmentioning
confidence: 99%
“…, but see Long et al. ), which are more sensitive to heat compared to heterotrophic bacteria (Dunn et al. ).…”
Section: Discussioncontrasting
confidence: 78%
“…Our work showed that burning treatment has no significant impact on 16S rRNA and denitrification gene abundance despite the contrasting impacts of fire treatments on the soil properties in the wet and dry forests. Long et al (2014) also reported that there was no significant difference in the 16S rRNA gene abundance between different burning treatments at the Peachester site. Nevertheless, observation of the fungal community showed a significant decline in response to the long-term prescribed burning (Bastias et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, a *Address correspondence to C. R. Chen, Environmental Futures number of studies have supported the idea that microbial communities was resistant to change (Fenchel and Finlay 2004;Long et al 2014). This was attributed to the common traits of microbes, such as vast abundance (>10 9 ), fast growth rates and rapid evolution (Torsvik 2002).…”
Section: Introductionmentioning
confidence: 99%